Preclinical orofacial pain assays and measures and chronic primary orofacial pain research: where we are and where we need to go - Sadighparvar, Shirin; Al-Hamed, Faez Saleh; Sharif-Naeini, Reza; Meloto, Carolina Beraldo (Frontiers in Pain Research, 2023)
Chronic primary orofacial pain (OFP) conditions such as painful temporomandibular disorders (pTMDs; i.e., myofascial pain and arthralgia), idiopathic trigeminal neuralgia (TN), and burning mouth syndrome (BMS) are seemingly idiopathic, but evidence support complex and multifactorial etiology and pathophysiology. Important fragments of this complex array of factors have been identified over the years largely with the help of preclinical studies. However, findings have yet to translate into better pain care for chronic OFP patients. The need to develop preclinical assays that better simulate the etiology, pathophysiology, and clinical symptoms of OFP patients and to assess OFP measures consistent with their clinical symptoms is a challenge that needs to be overcome to support this translation process. In this review, we describe rodent assays and OFP pain measures that can be used in support of chronic primary OFP research, in specific pTMDs, TN, and BMS. We discuss their suitability and limitations considering the current knowledge of the etiology and pathophysiology of these conditions and suggest possible future directions. Our goal is to foster the development of innovative animal models with greater translatability and potential to lead to better care for patients living with chronic primary OFP.